2010
DOI: 10.1029/2010sw000567
|View full text |Cite
|
Sign up to set email alerts
|

Galactic cosmic ray radiation hazard in the unusual extended solar minimum between solar cycles 23 and 24

Abstract: 1] Galactic cosmic rays (GCRs) are extremely difficult to shield against and pose one of the most severe long-term hazards for human exploration of space. The recent solar minimum between solar cycles 23 and 24 shows a prolonged period of reduced solar activity and low interplanetary magnetic field strengths. As a result, the modulation of GCRs is very weak, and the fluxes of GCRs are near their highest levels in the last 25 years in the fall of 2009. Here we explore the dose rates of GCRs in the current prolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 35 publications
3
28
1
Order By: Relevance
“…The GCR intensity modulation in the minimum 23/24 is also a broadly investigated subject because of its very unusual character (e.g., Heber et al, 2009;McDonald, Webber, and Reames, 2010;Schwadron et al, 2010). Recently, Paouris et al (2012) studied the GCR modulation in the minimum 23/24 in relation to solar activity indices and heliospheric parameters, such as the sunspot number, the interplanetary magnetic field, the CME index, and the tilt angle of the heliospheric current sheet.…”
Section: Introductionmentioning
confidence: 99%
“…The GCR intensity modulation in the minimum 23/24 is also a broadly investigated subject because of its very unusual character (e.g., Heber et al, 2009;McDonald, Webber, and Reames, 2010;Schwadron et al, 2010). Recently, Paouris et al (2012) studied the GCR modulation in the minimum 23/24 in relation to solar activity indices and heliospheric parameters, such as the sunspot number, the interplanetary magnetic field, the CME index, and the tilt angle of the heliospheric current sheet.…”
Section: Introductionmentioning
confidence: 99%
“…4) may indicate that an inhibiting effect on the prediction outcome due to complex interplanetary conditions between the Sun and Earth is indeed real. It is noted that the decay phase of solar cycle 23 was characterized by an unusual period of reduced solar activity and low interplanetary magnetic field strengths (Schwadron et al, 2010). Also, these authors reported that the extended solar minimum of 2009-2010, which extended between solar cycles 23 and 24, was marked by fluxes of galactic cosmic ray radiation at near to their highest level in 25 years.…”
Section: Possible Influence On the Predictions Of The Phase Of The Somentioning
confidence: 87%
“…These parameters affected other heliospheric conditions including the galactic cosmic ray flux (e.g. Schwadron et al 2010). The altered solar wind dynamic pressure also had significant impacts on planetary plasma interactions and geomagnetic activity.…”
Section: Introductionmentioning
confidence: 99%